The Mediating Role of Social Support and Resilience Between HIV-Related Stigmas and Patient Activation Among Young Black Women Living With HIV in the Southern United States: A Cross-sectional Study. (10th January 2022) - Chapman Lambert, Crystal; Fazeli, Pariya L.; Yigit, Ibrahim; Elopre, Latesha; King, Kiko; Kempf, Mirjam-Colette; Guthrie, Barbara; Mugavero, Michael J.
Abstract: Little is known about the construct of patient activation for engaging in favorable self-management behaviors in people with HIV. We conducted a cross-sectional study among young Black women with HIV ( n = 84) to examine the association between stigma and patient activation and the mediating role of social support and resilience. Social support mediated the relationship between the following dimensions of stigma and patient activation: internalized (β = −0.20, SE = 0.08, CI [−0.369 to −0.071]) and anticipated in health care settings (β = −0.06, SE = 0.04, CI [−0.177 to −0.001]). Resilience mediated the relationship between the following dimensions of stigma and patient activation: anticipated in health care (β = −0.20, SE = 0.08, CI [−0.387 to −0.057]) and community settings (β = −0.15, SE = 0.08, CI [−0.318 to −0.017]), and enacted in community settings (β = −0.14, SE = 0.09, CI [−0.332 to −0.001]). Our findings suggest intrapersonal and interpersonal mechanisms by which various dimensions of stigma contribute to patient activation, thus identifying social support, resilience, and patient activation as potential intervention targets.